1986
DOI: 10.1044/jshd.5104.337
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Understanding of Developmental Language and Reading Disorders

Abstract: The primary purpose of this study was to compare the ability of language-impaired and reading-impaired children to process (i.e., encode and retrieve) phonological information. Four measures of phonological awareness and several measures of word and sentence repetition abilities were used to evaluate phonological processing skills. Two additional measures assessed children's awareness of lexical and morphological information. Subjects were 12 language-impaired (LI), 12 reading-impaired (RI), and 12 normal chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
202
3
14

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(240 citation statements)
references
References 38 publications
21
202
3
14
Order By: Relevance
“…Although the mean performance of 7+ and 8+ year-old children with language impairments was average, 36.84% of 7+ year-olds and 29.63% of 8+ year-old children with language impairments scored at below average levels. These deficits found in auditory receptive abilities of children with language impairments support studies in English by various researchers (Kamhi & Koenig, 1985;Kamhi & Catts, 1986).…”
Section: Auditory Receptionsupporting
confidence: 62%
“…Although the mean performance of 7+ and 8+ year-old children with language impairments was average, 36.84% of 7+ year-olds and 29.63% of 8+ year-old children with language impairments scored at below average levels. These deficits found in auditory receptive abilities of children with language impairments support studies in English by various researchers (Kamhi & Koenig, 1985;Kamhi & Catts, 1986).…”
Section: Auditory Receptionsupporting
confidence: 62%
“…Many studies have reported that individuals with dyslexia perform more poorly on pseudoword repetition than control participants (e.g. Brady, Poggie, & Rapala, 1989;Brady, Shankweiler, & Mann, 1983;Hulme & Snowling, 1992;Kamhi & Catts, 1986;Snowling, 1981;Snowling, Goulandris, Bowlby, & Howell, 1986;Van Bon & Van Der Pijl, 1997;Van Daal & van der Leij, 1999), compatible with the notion that a phonological core deficit provides a causal explanation for dyslexia. But note that Reis and Castro-Caldas (1997) found that illiterates also performed much worse than literates on pseudoword repetition (replicated in Castro-Caldas, Petersson, Reis, Stone-Elander, & Ingvar, 1998).…”
Section: Pseudoword Repetitionmentioning
confidence: 85%
“…Goswami, 2003; and many others, see also Blomert, 2011;Olulade, Napoliello, & Eden, 2013;Saksida et al, 2016;Vellutino, Fletcher, Snowling, & Scanlon, 2004;Wimmer & Schurz, 2010, for recent discussions); that dyslexia is "a deficit in visuospatial attention, not in phonological processing" (Vidyasagar & Pammer, 2010); that "it is illogical to conclude that absence of evidence for some aspects of a magnocellular deficit in some dyslexics is evidence of its absence in all" (Stein, Talcott, & Walsh, 2000); that phonological and magnocellular deficit accounts both fail "to account for the full range of deficits established for dyslexic children … the full range of deficits might be accounted for in terms of a cerebellar deficit" (Nicolson, Fawcett, & Dean, 2001); and that "the cerebellum might stand unfairly accused, an innocent bystander in the processes responsible for disordered motor control in developmental dyslexia … the 'cerebellar' signs and symptoms associated with developmental dyslexia reflect a remote effect of neocortical perisylvian damage on cerebellar function" (Zeffiro & Eden, 2001). It has even been suggested that developmental dyslexia and specific language impairment are points on a continuum of learning disorders rather than distinct disabilities (Kamhi & Catts, 1986;cf. Tallal, Allard, Miller, & Curtiss, 1997; but see Bishop & Snowling, 2004;Norbury, 2014;Reilly, Bishop, & Tomblin, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The same criterion was used by Beitchman, Nair, Clegg, and Patel (1986), Catts (1993), and Kamhi and Catts (1986) to identify impaired oral language. Table 4 illustrates the number and percentage of children with an SRD who had impaired oral language in the four studies separately and combined.…”
Section: Resultsmentioning
confidence: 99%